Lesson Study Berkolaborasi Mengubah Tradisi Pembelajaran Sejarah - Afandi, Zainal (Efektor, 2018)
History is a subject that has a strategic role in the formation of the character and civilization of a dignified nation. But in reality the subject of history is less favored by learners. One of the contributing factors is the tradition of historical learning. There are still many history teachers who teach by relying on the ability of rhetoric regardless of the characteristics of learners. Therefore history teachers should change the tradition of learning history. Changes in history learning tradition must be done systematically and continuously. For that history teachers need to collaborate and synergize in making changes in historical teaching tradition. The right step is with Lessson Study activities because teachers / lecturers can conduct collaborative and continuous learning lessons to test and improve the effectiveness of learning. Lesson Studydi Activities History Study program is conducted with subject of study subject study of History of Indonesia 1945-1965. This activity is done through three stages, namely plan, do, and see. Data collection techniques were conducted with participant observation, while data collection instruments used observation guidelines. The results of data collection were analyzed using descriptive technique, ie by describing the systematic steps undertaken by Lesson Study team in changing history learning tradition. The historical teaching tradition that is still fixed on the paradigm of information forwarding and involves only low cognitive skills that is memorized has been successfully changed through Lesson Study activities. By collaborating and synergizing the changes in historical learning tradition can be systematic and sustainable. This condition is now beginning to be seen in the course of History Education. Although not yet running optimally, slowly but surely, the lecturer of the course of History Education has managed to change the tradition of learning. The habit of lecturers who often dominate the lesson by doing lectures while being ethical can be transformed into student-centered learning. The old habits of students who tend to be only fun listening to the explanation of lecturers to do a lot of activity to mengkrruksi knowledge. Therefore Lesson Study activities should be continued and optimized for implementation.